Awareness of Most Commonly Used Drugs in Dentistry Inducing Teratogenic Effects among Dental Practitioners (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The aim of the study was to assess the awareness of most commonly used drugs in dentistry inducingteratogenic effects, among dental practitioners. Birth defects may be caused by many factors such as physicalconditions, teratogens, environmental exposures, genetic defects, etc., Although prescription drug use iscommon during pregnancy, the human teratogenic risks are undetermined for more than 90% drug treatmentsapproved in the USA during the past decades. A particular birth defect may have its origins through multiplemechanisms and possible exposures including medications. A specific chemical process may result indifferent outcomes depending upon factors such as embryonic age at which a drug is administered, durationand dose of exposure and genetic susceptibility. Estimating the risk of fetal malformations attribute to theuse of medications is difficult and perception of risk by health professionals will impact their counseling andtreatment of patients. Pregnancy is a unique physiologic condition and importantly specific drugs like folicacid use may have several benefits for pregnant mother. The patient should maintain a good gynecologistpatient-Dentist communication. For example a woman with two spontaneous abortions would be expectedto be skeptical of any drug therapy in her next pregnancy and by communicating this to physicians andrespective clinician. She may influence the physician and dentist perception. The clinician should be awareof all the newer drugs and its teratogenic effects. For health professionals this includes awareness of specificdrug information and sources that provide realistic descriptions of risk beyond product monographs. Agreater focus on this aspect may act to balance Risk perceptions. Physicians and dentists need to weigh risksand benefits of drug prescribing to pregnant patients based on the available knowledge.